Smart fuzzy logic control of photovoltaic system: case study Kingdom of Saudi Arabia - Taha A. Khalaf; Khalid Alshahrani; Obaid Alsubaie; Anas Aljohani; Waleed AlAnzi; Mahmoud Aref (Institute of Advanced Engineering and Science, 2023)
Robust controls of photovoltaic (PV) system applications that include modular multilevel inverter (MMI) for interfacing stand-alone and gridconnected operating modes are investigated in this paper to overcome interfacing problems of two-level and three-level inverters. The MMI provides high-quality voltage, current, and power signals without additional filters, which reduces complexity and cost of interface circuits. A new control method of active and reactive power has been introduced for PV systems to get maximum power point (MPP) in various climatic circumstances. The steady-state and dynamic performances of MMI are investigated using MATLAB/Simulink. A fuzzy logic control is proposed to track the MPP utilizing the perturb and observe (P&O) technique. A fair comparison between fuzzy logic control and proportional integral (PI) control was conducted using MATLAB/Simulink. The fuzzy logic controller for obtaining MPPT by P&O method is proposed to get fast and accurate results. The obtained results obvioused that the fuzzy logic controller is quick accessing MPP than PI controller. A simple LC filter can achieve minimum harmonics provided by total harmonic distortion (THD) of MMI within IEEE limit. The PV system for standalone and grid-connected modes is being tested under climatic conditions in the city of Tabuk, Kingdom of Saudi Arabia (KSA).